Cabbage production in function of castor bean cake doses in top dressing - Magro, Felipe Oliveira; Vianou Lorentz Hounmenou, Gilles; Secchi Candian, Joara; Ayumi Inowe, Mayara; Fernandes Colombari, Lidiane; Inácio Cardoso, Antonio Ismael (Comunicata Scientiae, 2021)
The researches with organic fertilization in top dressing in production of vegetables are rare, thereby, the objective of this study was to evaluate castor bean cake doses in top dressing in cabbage production. Seven treatments, six castor bean cake doses in top dressing (0; 50; 100; 150; 200 and 250 g m-2) and an inorganic control with ammonium sulphate (11.5 g m-2 of N) and potassium chloride (5.4 g m-2 of K2O) in top dressing were evaluated, in randomized blocks experimental design, with five replicates. Before planting it was made fertilization with organic compost (20 t ha-1) and inorganic NPK fertilizer (4-14-8) (1 t ha-1), only in inorganic control. The characteristics evaluated were: cabbage head diameter, height, number of leaves, fresh and dry weight of cabbage. The application of castor bean cake in top dressing increased the diameter, height, number of leaves, fresh and dry weight of cabbage, with maximum values of 164 mm, 109 mm, 30 leaves, 1470 g and 103 g, respectively. The average fresh and dry weight obtained in the two highest doses of castor bean cake did not differ from the inorganic control, proving the technical viability of its using. Therefore, it can be recommended application of at least 200 g m-2 of castor bean cake in top dressing for cabbage production.